Modelling a family of systems for crisis management with concern‐oriented reuse. (16th November 2016) - Alam, Omar; Kienzle, Jörg; Mussbacher, Gunter
Summary: Concern‐oriented reuse (CORE) proposes the concern as a new unit of model‐based reuse encapsulating software artefacts pertaining to a domain of interest that span multiple development phases and levels of abstraction. With CORE, a concern encapsulates multiple reusable features, while allowing its generic models to be customized to problem‐specific contexts. We report on our experience of designing a family of crisis management systems (CMS) with the help of reusable concern libraries. The collected metrics show a considerable amount of reuse in our CMS design. The study provides encouraging evidence that CORE's vision to create large‐scale, generic and reusable entities that are expressed with the most appropriate modelling formalisms at the right level of abstraction is feasible. We present our experience in the design of the CMS and elaborate on the advantages as well as the efforts required to adopt CORE in an industrial setting. Copyright © 2016 John Wiley & Sons, Ltd.